Oxidative Stress and Antioxidant Status in Patients of acute Myocardial Infarction before and after Regular Treatment (University Heart Journal, 2015)
In acute myocardial infarction (AMI), generation of free radicals contribute to its pathogenesis. We evaluated the extent of oxidative stress and its amelioration in AMI patients after regular treatment and assessed its association with risk factors like dyslipidemia and diabetes mellitus (DM). Plasma MDA level increased (p